Poetry at Stake Lyric Aesthetics and the Challenge of Technology - Noland, Carrie (Princeton University Press, 2022)
Taking seriously Guillaume Apollinaire's wager that twentieth-century poets would one day "mechanize" poetry as modern industry has mechanized the world, Carrie Noland explores poetic attempts to redefine the relationship between subjective expression and mechanical reproduction, high art and the world of things. Noland builds upon close readings to construct a tradition of diverse lyricists--from Arthur Rimbaud, Blaise Cendrars, and René Char to contemporary performance artists Laurie Anderson and Patti Smith--allied in their concern with the nature of subjectivity in an age of mechanical reproduction
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: LITERARY CRITICISM / Poetry; Aesthetics, Modern; French poetry -- 19th century -- History and criticism; French poetry -- 20th century -- History and criticism; Literature and technology -- France; Literature and technology -- United States; Lyric poetry -- History and criticism